2016
DOI: 10.1158/1940-6207.capr-16-0032
|View full text |Cite
|
Sign up to set email alerts
|

2-Phenethyl Isothiocyanate, Glutathione S-transferase M1 and T1 Polymorphisms, and Detoxification of Volatile Organic Carcinogens and Toxicants in Tobacco Smoke

Abstract: Cigarette smoke contains relatively large quantities of volatile organic toxicants or carcinogens such as benzene, acrolein and crotonaldehyde. Among their detoxification products are mercapturic acids formed from glutathione conjugation, catalyzed in part by glutathione S-transferases (GST). A randomized phase 2 clinical trial with a crossover design was conducted to evaluate the effect of 2-phenethyl isothiocyanate (PEITC), a natural product formed from gluconasturtiin in certain cruciferous vegetables, on t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 50 publications
1
34
0
Order By: Relevance
“…Another finding that needs in vivo clarification is that PEITC can covalently modify the cysteine side chains of GST in vitro and in silico, which irreversibly inhibit the enzymatic activity of GST . Based on the in vitro finding, PEITC consumption should decrease, rather than increase, urinary concentrations of mercapturic acid metabolites of benzene, as observed in vivo by Yuan et al . Although a limited number of clinical trials used endpoints relevant to lung carcinogenesis to date, we found two trials in ClinicalTrials.gov that proposed to measure indicators of pulmonary inflammation, dysplasia, proliferation, or apoptosis, which would help further elucidate potential effects of ITCs for lung cancer prevention.…”
Section: Clinical Studies Of Cruciferous Vegetable or Itc Intake For mentioning
confidence: 74%
See 1 more Smart Citation
“…Another finding that needs in vivo clarification is that PEITC can covalently modify the cysteine side chains of GST in vitro and in silico, which irreversibly inhibit the enzymatic activity of GST . Based on the in vitro finding, PEITC consumption should decrease, rather than increase, urinary concentrations of mercapturic acid metabolites of benzene, as observed in vivo by Yuan et al . Although a limited number of clinical trials used endpoints relevant to lung carcinogenesis to date, we found two trials in ClinicalTrials.gov that proposed to measure indicators of pulmonary inflammation, dysplasia, proliferation, or apoptosis, which would help further elucidate potential effects of ITCs for lung cancer prevention.…”
Section: Clinical Studies Of Cruciferous Vegetable or Itc Intake For mentioning
confidence: 74%
“…A limitation of many clinical trials is the small sample size, which limits investigators’ ability to detect statistically significant group differences, account for effect modification as well as result reporting. For example, the Minnesota study was not designed to adequately evaluate effect modification by GST genotypes, as the sample size in genotype groups was small (19–63 participants per group). In comparison, the sample size in the Qidong study was adequate (46–74 participants per group).…”
Section: Clinical Studies Of Cruciferous Vegetable or Itc Intake For mentioning
confidence: 99%
“…A study conducted among smokers showed that watercress consumption promotes a higher excretion of glucuronidated nicotine in urine indicating activation of the phase II enzyme UDP-glucuronosyltransferase (UGT) ( 80 ). Most recently, Yuan et al, in a randomized, placebo-controlled, double-blind study conducted among smokers found a greater excretion of the mercapturic acids of benzene and acrolein (substances of tobacco smoke) in urine after oral administration of PEITC for 5 days ( 81 ). In addition, human polymorphisms for the GST gene that affect their activity have been described ( 82 ).…”
Section: Biological Effects Of Itcs and Mechanismsmentioning
confidence: 99%
“…In a recent study in which smokers were administered PEITC (10 mg, 4 times a day), the PEITC arm reduced metabolic activation of NNK, one of the most potent lung carcinogens present in cigarettes by 7.7% [54]. Larger increases in rates of excretion of detoxication metabolites (often mercapturic acids) of combustion pollutants such as benzene and aldehydes were observed following PEITC intervention [55] (Figure 2). Similar trends in modulating metabolism of air pollutants by broccoli sprout beverages had been observed in our group in two previous trials.…”
Section: Clinical Trials With Disease-related Outcomes Using Isothiomentioning
confidence: 99%